Phenol and Phthalate Effects on Thyroid Hormone Levels during Pregnancy: Relying on In Vitro Assays and Adverse Outcome Pathways to Inform an Epidemiological Analysis - Nakiwala, Dorothy; Noyes, Pamela D.; Faure, Patrice; Chovelon, Benoît; Corne, Christelle; Gauchez, Anne Sophie; Guergour, Dorra; Lyon-Caen, Sarah; Sakhi, Amrit K.; Sabaredzovic, Azemira; Thomsen, Cathrine; Pin, Isabelle; et al. (Environmental health perspectives, 2022)
Studies characterizing associations between phenols, phthalates and thyroid hormones during pregnancy produce inconsistent results. This divergence may be partly attributable to false positives due to multiple comparison testing of large numbers of chemicals, and measurement error as studies rely on small numbers of biospecimens despite high intra-individual variability in urinary chemical metabolite concentrations. This study employs chemical filtering and expanded urinary biomonitoring to evaluate associations between phenol/phthalate exposures and serum thyroid hormones assessed during pregnancy. A two-tiered approach was implemented: ) high-throughput screening results from the ToxCast/Tox21 database, as informed by a thyroid Adverse Outcome Pathway network, were evaluated to select phenols/phthalates with activity on known and putative molecular initiating events in the thyroid pathway; and ) Adjusted linear regressions were used to study associations between filtered compounds and serum thyroid hormones measured in 437 pregnant women recruited in Grenoble area (France) between 2014 and 2017. Phenol/phthalate metabolites were measured in repeated spot urine sample pools (median: 21 samples/women). The ToxCast/Tox21 screening reduced the chemical set from 16 to 13 and the associated number of statistical comparisons by 19%. Parabens were negatively associated with free triiodothyronine (T3) and the T3/T4 (total thyroxine) ratio. Monobenzyl phthalate was positively associated with total T4 and negatively with the T3/T4 ratio. Effect modification by iodine status was detected for several compounds (among them and mono- -butyl phthalate) that were associated with some hormones among women with normal iodine levels. For these chemicals, screening for compounds with an increased likelihood for thyroid-related effects and relying on repeated urine samples to assess exposures improved the overall performance of multichemical analyses of thyroid disruption. This approach may improve future evaluations of human data for the thyroid pathway with implication for fetal health and may serve as a model for evaluating other toxicity outcomes. https://doi.org/10.1289/EHP10239.